Robust control of three phase VSI with LCL filter for distributed generation in microgrids enviroment - Pena, Jose Carlos U. [UNESP]; Canesin, Carlos A. [UNESP]; Sampaio, Leonardo P. (Institute of Electrical and Electronics Engineers (IEEE), 2015)
This paper proposes a methodology to model and control a three phase voltage source inverter (VSI) with LCL filter intended for distributed generation in microgrid scenario. Thus, the inverter should be able to operate in both grid-connected and islanded modes with a smooth transition between them. The strategy is to split the control input into two components. The first component is generated to make the voltages at capacitors to track sinusoidal references; meanwhile the second component is suitable to increase these voltages in order to achieve the certain amplitude and phase that guarantee the required output current. To obtain the controllers that generate these control signals, system is modeled in state-space and reduced to an equivalent single phase representation; state-feedback controllers are computed by means of Linear Matrix Inequalities solvers considering uncertainty on the grid inductance. Simulation results prove the validity of the proposed control system.
Keywords: Grid-connected inverter; LCL filter; Linear Matrix Inequalities (LMIs); Microgrid inverter; Robust control